Investigating Pre-service Social Studies Teachers' Global Social Responsibility Level - Enis Harun Baser; Emin Kilinc (ÜNİVERSİTEPARK Limited, 2015)
The purpose of this research is to investigate pre-service social studies teachers' global social responsibility levels from national, action-oriented, altruistic, and ecological aspects by considering gender, course year, academic success level, membership of a non-governmental organization, and where they lived before attending university. The author applied the descriptive survey model for this study in order to investigate pre-service social studies teachers' global social responsibility level. Participants of the study were selected through cluster random sampling from public universities in the Marmara, Aegean, and Central Anatolia regions of Turkey. The sample of the study consisted of 463 pre-service social studies teachers enrolled at either Afyon Kocatepe University, Usak University, Anadolu University, or Istanbul University. In order to analyze the data, one-way variance analysis (ANOVA), multiple comparison test (Post-Hoc) and independent samples t-test were used. The results indicated that there was no significant difference on participants' global social responsibility level by considering gender and course year. However, the results showed that pre-service social studies teachers who are members of any non-profit organization have higher levels of action-oriented responsibility, ecologic responsibility, and altruistic responsibility, than those who are not. Moreover, pre-service social studies teachers who lived in middle-sized city prior to attending university have more global social responsibility than those who lived in a village.